Comparing the clinical and radiographic outcomes of two different surgical approaches for treating infrabony defects in chronic periodontitis patients - Hiroj S Bagde; Mohammad K Alam; Yazan Eid Muteb Almohammed; Sufyan Mohammed Mukhlef Almaqawid; Kiran K Ganji; Mohammed G Sghaireen (Wolters Kluwer Medknow Publications, 2024)
Background: Chronic periodontitis is a prevalent oral health issue, affecting a substantial portion of the population. Infrabony defects, characterized by bone loss around teeth, are a hallmark of this condition and require surgical intervention to prevent further damage and tooth loss. Two commonly used surgical approaches are open flap debridement (OFD) and guided tissue regeneration (GTR). Materials and Methods: This prospective cohort study included 60 patients with chronic periodontitis and infrabony defects. Patients were randomly assigned to either the OFD or GTR group. Clinical parameters, including probing depth (PD) and clinical attachment level (CAL), were recorded at baseline and at 6-month and 12-month follow-up appointments. Radiographic assessments were conducted using periapical radiographs. The primary outcome measures were changes in PD and CAL, while secondary outcomes included radiographic evidence of bone regeneration. Results: At the 6-month follow-up, the OFD group demonstrated an average reduction in PD of 2.4 mm (SD = 0.8) and an increase in CAL of 1.6 mm (SD = 0.5). In contrast, the GTR group showed a reduction in PD of 2.1 mm (SD = 0.7) and an increase in CAL of 1.9 mm (SD = 0.6). These differences were not statistically significant (P > 0.05). Radiographic analysis indicated a mean bone fill of 1.2 mm (SD = 0.4) in the OFD group and 1.4 mm (SD = 0.3) in the GTR group at 12 months, with no significant difference observed between the two groups (P > 0.05). Conclusion: In this study, both OFD and GTR approaches demonstrated comparable clinical and radiographic outcomes in the treatment of infrabony defects in chronic periodontitis patients.